Hubungan Kondisi Lingkungan Fisik rumah dan Kejadian ISPA di Kelurahan Bener, Tegalrejo, Yogyakarta, Tahun 2014 - Deavita Intan Pradani; Sri Muryani; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
As the medium for life development and the place for family member to get on together spending most of their times, a house shoud be healthy and comfortable. Unhealthy house is closely related with the increase of ARI incidence, which is included in the top 10 diseases among the service area of Tegalrejo Community Health Centre. A preliminary survey held in Kelurahan Bener, showed that 39% houses were identified unhealthy, 53% less healthy, and only 8% were healthy. This study were aimed to determine the relationship between house physical environment condition and ARI incidence in that kelurahan by conducting a retrospective case-control study. Member of the case group were 30 new ARI cases sought for medication to the community healthcentre who were sampled randomly; meanwhile as the control group, 30 non-ARI close neighbors who have similar characteristics with each case were selected. The observation of the physical condition parameters, i.e. ventilation width, and indoor temperature, humidity and lighting, was using proper instruments and were averaged from three measurements. The results show that the parameters under study which have significant association with ARI incidence are: indoor humidity (OR: 3,82; 95% CI: 1,15-12,71; p-value: 0,024) and indoor lighting (OR: 4,00; 95% CI: 1,37-11,70; p-value: 0,009); meanwhile, those which are not related, are ventilation width (OR: 1,80; 95% CI: 0,39-8,32; p-value: 0,448) and indoor temperature (OR: 3,79; 95% CI: 0,75-10,33; p-value: 0,117).